Morphological Disparity of the Humerus in Modern Birds - Serrano Alarcón, Francisco José; Costa-Pérez, Mireia; Navalón, Guillermo; Martín-Serra, Alberto (MDPI, 2020)
From a functional standpoint, the humerus is a key element in the skeleton of vertebrates as it is the forelimb's bone that connects with the pectoral girdle. In most birds, the humerus receives both the forces exerted by the main flight muscles and the aerodynamical stresses exerted upon the wing during locomotion. Despite this functional preeminence, broad scale studies of the morphological disparity of the humerus in the crown group of birds (Neornithes) are lacking. Here, we explore the variation in shape of the humeral outline in modern birds and its evolutionary relationship with size and the evolution of different functional regimes, including several flight strategies, wing propelled diving and complete loss of wing locomotory function. Our findings suggest that most neornithines evolved repeatedly towards a general humeral morphology linked with functional advantages related with more efficient flapping. Lineages evolving high-stress locomotion such as hyperaeriality (e.g., swifts), hovering (e.g., hummingbirds) and wing-propelled diving (e.g., penguins) greatly deviate from this general trend, each exploring different morphologies. Secondarily flightless birds deviate to a lesser degree from their parent clades in humeral morphology likely as a result of the release from constraints related with wing-based locomotion. Furthermore, these taxa show a different allometric trend that flighted birds. Our results reveal that the constraints of aerial and aquatic locomotion are main factors shaping the macroevolution of humeral morphology in modern birds.
Keywords: Húmeros; Wing-propelled diving; Neornithes; Geometric morphometrics; Flightlessness; Avian flight; Allometry; Avian Humerus